Wild Medicinal Plants of Jaunsar-bawar Western Himalaya, Uttarakhand - Bisht, D. S.; Pundir, Y. P. S. (Indian Forester, 2014)
The paper reports sixty seven wild medicinal plants used by the natives of Jaunsar-Bawar (Western Himalaya), Uttarakhand. A list of additional 116 wild medicinal plants already reported from this area by the authors is also given.